Advancement of insects as food and feed in a circular economy - Fels-Klerx, Ine van der,; Huis, Arnold van,; Rumpold, Birgit,; Tomberlin, Jeffrey, (Life Sciences E-Book Collection, 2025., 2025)
In 2017, a book was published entitled 'Insects as food and feed: from production to consumption' (Van Huis and Tomberlin, 2017). However, the sector of insects as food and feed is developing so quickly that an update seems appropriate. This book 'Advancement of insects as food and feed in a circular economyy' is a reprint of the Special Isse in Open Access in the Journal of Insects as Food and Feed. All chapters dealt with relevant topics related to insects as food and feed, and most of the content of the articles is different from the 2017 book, reflecting developments in the field.